1996
DOI: 10.1177/0361198196154500107
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Low-Temperature Cracking of Asphalt Concrete Mixtures with Thermal Stress Restrained Specimen Test Results

Abstract: A deterministic model and a probabilistic model were developed to predict low-temperature crack spacing as a function of time using thermal stress restrained specimen test results, pavement thickness and bulk density, pavement restraint conditions, and air temperature. The effect of aging on pavement properties was incorporated in the models by predicting the field aging with long-term oven aging treatment in the laboratory. The calculation of the crack spacing is based on the theory that the pavement slab cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Additionally, thermal cracking is a common phenomenon in cold regions, and through these cracks water can ingress to the pavement structure [6]. Thermal cracking is associated with the contraction that the pavement suffers at low temperature, and happens when the induced thermal stress is higher than the tensile strength of asphalt concrete at that temperature [7].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, thermal cracking is a common phenomenon in cold regions, and through these cracks water can ingress to the pavement structure [6]. Thermal cracking is associated with the contraction that the pavement suffers at low temperature, and happens when the induced thermal stress is higher than the tensile strength of asphalt concrete at that temperature [7].…”
Section: Introductionmentioning
confidence: 99%
“…As an accelerated performance test developed during the Strategic Highway Research Program (SHRP), the thermal stress restrained specimen test (TSRST) was widely applied to simulate lowtemperature cracking of asphalt concrete [1][2][3][4]. Beam or cylindrical specimens with a length of 250 mm are required in this test, whereby thermally-induced stress within the specimen develops until fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research (1)(2)(3)(4)(5)(6) has shown that the structural performance of asphalt mixtures containing RAP is generally similar to that of the conventional virgin asphalt mixtures. This research also showed that the properties of the mixtures containing RAP are influenced mainly by the aged RAP binder properties and the amount of RAP in the mixture.…”
mentioning
confidence: 99%